Using activity-based teaching in enhancing students skills in performing addition and subtraction of integers - Crelyn Joy C. Cabajar; Christine F. Canedo, and Marijoy P. Catalon. 4 0 16; 5 (2016)
ABSTRACT: One serious struggle of students in learning higher mathematics is not having a strong foundation of adding and subtracting integers. This study focuses on data gathered from seventh grade mathematical class. The researcher analyzed the effect of various activities using improvised models, cards war, 4 pics one word and cooperative problem solving. The results assessed students skills is recognizing clue words, solving word problems, relating temperature with integers and symbolic addition and subtraction of integers. These activities enhanced skills of students in performing addition and subtraction of integers. Results were compared using the same assessment tool, the pretest and posttest. Informal interviews with the teacher and students and a survey is conducted. The combination of these data suggests that students skills are enhanced when using Activity-based teaching.
Thesis: (Bachelor of Secondary Education with Specialization in Mathematics) - Pamantasan ng Lungsod ng Maynila, 2016.
Keywords: 2 -- 0; 6; 20; 20; 2